The Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Pembelian Produk Olahan Ikan Griyaulam-Q Kabupaten Kediri - Fatmawati, Erlin Widya; Navita Maharani; Nastiti Winahyu (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
The government is aggressively implementing the Gemari program, namely Gemar Makan Ikan, to improve community nutrition. Fish processors use this opportunity to make varied fish dishes. Processed fish products are essential to increase consumer interest in consuming processed fish. This research aims to determine the influence of product quality on purchasing decisions, determine the influence of product prices on purchasing decisions for processed fish products, and determine the influence of product promotions on purchasing decisions for processed fish products at Griya Ulam-Q, Kediri Regency. The method used for objective analysis in this research is quantitative with multiple linear regression using SPSS. The regression analysis results in this research show in the t-test that product quality and promotion significantly affect purchasing decisions for processed fish products at Griya Ulam-Q, Kediri Regency. Meanwhile, the price variable only significantly affects the decision to purchase processed fish products at the Griya Ulam-Q.